Bacterial and Parasitic Assessment from Fingernails in Debre Markos, Northwest Ethiopia - Abeba Mengist; Yibeltal Aschale; Alemayehu Reta (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Food handlers with untrimmed finger nails could contribute or serve as a vehicle for the transmission of food poisoning pathogens. Objectives. This study was conducted to determine the prevalence of bacteria and intestinal parasites among food handlers and antibiotic susceptibility profile of the isolated bacteria in Debre Markos University, Ethiopia. Materials and Methods. This laboratory-based cross-sectional study involved 220 food handlers working in food service establishments in Debre Markos University between 1st January 2015 to 31th June 2016. Subjects’ finger nail specimens of both hands were examined microscopically for intestinal parasites. For bacterial isolation, samples were cultured and bacterial species were identified following standard laboratory procedures. Antimicrobial susceptibility test was performed for all bacterial isolates by using Kirby-Bauer disk diffusion method. Results. Of the total 220 subjects examined, 29.5% showed positive culture for different bacterial species from their fingernail contents. Coagulase-negative Staphylococcus was the predominant bacteria species (12.3%) followed by Staphylococcus aureus (5%), E. coli (2.7%), Klebsiella species (2.7%), Enterococcus species (1.8%), Pseudomonas aeruginosa (1.8%), Proteus species (1.4%), Citrobacter species (1.4%), and Serratia species (0.9%). None of the food handlers showed positive culture for Shigella and salmonella and parasites in respect of their finger nail specimens. Isolation of bacteria in finger nail has significant association with finger nail status (P=0.044) and inverse relation with service years (P=0.048). All Staphylococcus aureus and coagulase-negative Staphylococcus species isolates were uniformly susceptible to vancomycin. Only one (9.1%) of Staphylococcus aureus isolates was resistant for methicillin. Conclusion. To prevent the food poisoning pathogens, implementation and adherence to infection are the key practices, specially food handlers with long finger nail harbor food debris, microbial contaminations, and allergens.